Tubos de concreto produzidos com fibras de aço e agregados da região metropolitana de Belém do Pará - Oliveira, Marco Antonio Barbosa de (2017)
Reinforced steel-fiber concrete pipes emerge as an interesting technological variant. In an incipient study of the locality, the main objective was to assess the technical feasibility of discontinued reinforced steel-fiber concrete pipes randomly oriented by the diametrical compression test for mechanical behaviour analysis. The second objective was to verify the water absorption and effective fiber content in the spigot, barrel and bell of the tube. In this study, DRAMIX 80/60 or 65/35 steel fibers were used (loose or glued) in the theoretical contents of 0.25%, 0.38% and 0.50%. The results indicated that the concrete pipes from the TCFA 80/60 – FCP series in the effective fiber contents of 0.36% and 0.50% and the TCFA 80/60 – FS series in all effective contents were the only ones that reached the minimum failure loading and post-cracking established by the NBR 8900 (ABNT, 2007). The water absorption results were below the maximum absorption recommended by NBR 8900 (ABNT, 2007) and there were higher levels of absorption and effective fiber content in the chain from the order spigot, barrel and bell. Finally, the technical feasibility of reinforced steel-fiber concrete pipes in the locality was shown to be timely.